The Roman law of obligations - Birks, Peter, 1941-2004; Descheemaeker, Eric, 1977- (Oxford : Oxford University Press, 2014)
This volume contains Birks' notes on a series of lectures on the Roman law of obligations delivered in 1982. They give a comprehensive insight into his views on the topic, which are relevant in both a Roman context and also from a modern English perspective. The book examines, in turn, the law of contracts with its general principles and rule applications to the transactions mentioned in the Institutes; the law of delicts; and finally the miscellany of residual obligations from which the later categories of quasi-contracts and quasi-delicts, but also the modern law of unjust enrichment, emerged.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 2, 2014).
Keywords: Obligations (Roman law); Law